Release of HMGB1 and Toll-like Receptors 2, 4, and 9 Signaling Are Modulated by Bifidobacterium animalis subsp. lactis BB-12 and Salmonella Typhimurium in a Gnotobiotic Piglet Model of Preterm Infants - Splichal, Igor; Donovan, Sharon M; Kindlova, Zdislava; Stranak, Zbynek; Neuzil Bunesova, Vera; Sinkora, Marek; Polakova, Katerina; Valaskova, Barbora; Splichalova, Alla (International journal of molecular sciences, 2023)
Gnotobiotic (GN) animals with defined microbiota allow us to study host-microbiota and microbiota-microbiota interferences. Preterm germ-free (GF) piglets were mono-associated with probiotic Bifidobacterium animalis subsp. lactis BB-12 (BB12) to ameliorate/prevent the consequences of infection with the Salmonella Typhimurium strain LT2 (LT2). Goblet cell density; expression of Toll-like receptors (TLRs) 2, 4, and 9; high mobility group box 1 (HMGB1); interleukin (IL)-6; and IL-12/23p40 were analyzed to evaluate the possible modulatory effect of BB12. BB12 prevented an LT2-induced decrease of goblet cell density in the colon. TLRs signaling modified by LT2 was not influenced by the previous association with BB12. The expression of HMGB1, IL-6, and IL12/23p40 in the jejunum, ileum, and colon and their levels in plasma were all decreased by BB12, but these changes were not statistically significant. In the colon, differences in HMGB1 distribution between the GF and LT2 piglet groups were observed. In conclusion, the mono-association of GF piglets with BB12 prior to LT2 infection partially ameliorated the inflammatory response to LT2 infection.
Keywords: mucin; protein HMGB1; inflammatory cytokines; Bifidobacterium animalis subsp. lactis BB-12; Salmonella Typhimurium; Bifidobacterium animalis; Toll-Like Receptors; Toll-like receptors; HMGB1 Protein; probiotika; gnotobiologické modely; tight junction proteins; Probiotics; Infant, Newborn; Swine; high mobility group box 1; novorozenec; toll-like receptory; zvířata; Humans; Salmonella typhimurium; immunodeficient host; Germ-Free Life; Infant, Premature; intestinal barrier; prasata; novorozenec nedonošený; lidé; Animals